On Becoming Crisis Counselors: Malaysian Volunteers Experiences of helping During Disasters - Rais, Haniza (2014)

(untitled)
In the past few years, Malaysia has faced unexpected disasters, be it natural and man made, that has led to the immediate needs for professional helpers to provide psycho-emotional support to the affected people. The International Counseling Association of Malaysia (PERKAMA INTERNATIONAL) has been involved in providing assistance at different occasions as the National hit with unexpected disaster like flood disaster, Lahad Datu incident and flight disasters involving MH17 and MH 370. PERKAMA being one of the partners of the Malaysian Crisis Intervention Team (MCIT) has also assisted Sabahan children who were at that time national service trainee in West Malaysia during Lahad Datu incident. PERKAMA counselors were also involved as crisis volunteers in providing psycho-emotional assistance to the families and caregivers of the passengers and crew of MH370.  All the experiences have great impact on our counseling profession and counseling training in Malaysia. A qualitative study was conducted among the volunteers to explore their counseling professionals’ endeavors in helping people during these crises.